DYNAMICS OF SMALL PLAGIC FISH PRODUCTION AND ITS IMPLICATIONS FOR FOOD SECURITY IN COASTAL AREAS - Jannah, Baiq Miftahul (Politeknik Kelautan dan Perikanan Karawang, 2026)
Small pelagic fish are the backbone of Indonesia's capture fisheries, contributing the largest production volume with an economic value of Rp43 trillion by 2024, where the main commodities such as cob, kites, and mackerel dominate the catch. This study analyzes the production dynamics of small pelagic fish during the period 2020–2024 and the causal factors influencing supply fluctuations. The results of the analysis showed that the production dynamics of small pelagic fish were strongly influenced by bio-oceanographic variables, in particular Sea Surface Temperature (SPL) anomalies associated with the ENSO (El Niño Southern Oscillation) cycle and Chlorophyll-a concentration (primary productivity). In addition to natural factors, overfishing pressure, exacerbated by Illegal Fishing activities, distorts total effort and creates supply instability. The implications of this production dynamic are crucial for the food security of coastal communities, where the availability of small pelagic fish as an affordable source of animal protein is significantly correlated with nutritional levels and stunting prevention in children under five. Coastal areas with high access to fish protein show a much lower prevalence of stunting (3.1%) than non-coastal areas (26.9%), confirming small pelagic fish as a vital nutritional intervention. Therefore, a digital data-based adaptive management strategy (Decision Support System/DSS) and strengthening the implementation of measured fishing policies are needed to stabilize production and ensure the sustainability of protein supply for coastal communities.